A Bio-Inspired Territorial Predator Scent Marking Algorithm in Software-Defined Data Center - Hacham S.; Din N.M.; Balasubramanian N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Biomimetics; Forestry; Network architecture; Trees (mathematics); Data center networks; Data-transmission; Datacenter; Fat trees; Marking algorithm; Mininet; Openflow; Quality-of-service; Routing techniques; SDN; Quality of service